MENUJU PELAYANAN PUBLIK BEBAS KORUPSI, KOLUSI DAN NEPOTISME (KKN) - Sugiyarti, Sri Riris (Transformasi, 2012)
Abstract Corruptionis anact ofembezzlement ofstateresourcesbygovernment officials, collusion, the act of agovernment officialor politician andprivate businesses conduct covert cooperation by utilizing public cresources for personal or group interests, while nepotism deliberate attemptby an officer to take advantage of his position to benefit position, rank and career your self ,family or friends close by unfair an dunlawful. Keywords: Corruption; Collusion; Nepotism; Service